Khuruj and Family Economic Resilience: Study on Jama’ah Tabligh Family in Medan City - Nurhayati, Nurhayati (Al-Ahkam, 2019)
Khuruj for preach by leaving the family is a must for every member of Jama’ah Tabligh (JT). When khuruj time, JT members cannot conduct their duty as head of the interested household especially to fulfill family economic needs. It is often, they khuruj without leaving enough provision of needs for their family. It is understandable why JT members are often accused as a group that neglects their family not even caring for the family. This research objective is to analyze survival strategy and tactics of the JT family by using a qualitative method. The researcher will conduct an in-depth interview with JT members and their family. Through this field research is found that 1) JT family has a strong belief that their sustenance is the gift of God. 2) Provision of needs that is left by the husband is enough to be utilized as long as being managed with sincerity. 3) JT family has a special survival strategy. So, khuruj is a method of da’wah that does not disturb family economic resilience.